Game flow and attitude in computer-based business simulations: Implications for management education (Journal of Applied Learning and Teaching, 2025)
This research investigates the influence of computer-based business simulations on students’ perceived learning outcomes, emphasising the roles of game flow and attitude. Using structural equation modelling to analyse survey data from management undergraduates, the study finds that goal clarity, autonomy, and enjoyment significantly predict game flow, which, in turn, enhances perceived learning outcomes and promotes positive attitudes. Interestingly, attitude does not directly impact students’ perceived learning outcomes, pointing to potential moderating effects of individual and contextual factors. The findings extend the game flow theory in management education, offering practical recommendations for enhancing engagement through clear goals, autonomy, and enjoyment. They also underscore the importance of further examining factors that mediate the relationship between attitudes and learning outcomes.